HADIS PADA MASA NABI MUHAMMAD SAW DAN SAHABAT - Harahap, Radinal Mukhtar (Al-Bukh?r? : Jurnal Ilmu Hadis, 2018)
Discourses on hadith in the Prophet?s time and His companions are important in initiating study ulum al-hadith. This is because one of the function of hadith as the explanatory verses of the Koran. This article will try to elaborate some approaches of library research in ulum al-hadith (1) How the companions received, memorized applied those hadith in their life. (2) Commands and prohibitions were not generalized to all companions in writing hadith. (3) The maintenance of hadits at the companions era from lost and also from mingled with Qur?an. (4) Distributed those hadith to the vast area of Islam at the time (5) All narrators of hadith to be agreed by scholars as good people and behavior. (6) there were some criteria of fairness for companions (?ad?lah al-?a??bah), namely, Muslims, maturity, intelligent, piety, selfrespect, avoiding him self from cases of fasiq, to be acknowledge their fairness, and free from criticism of scholars.